Proposal of a Conceptual/Functional Model to Support New Product Development Design - Dias, Ana Sofia Martins da Eira (2017)
Innovation and creativity are fundamental for new product development (NPD). NPD processes are a key factor for the survival of firms, in a market that nowadays is very competitive, instable and aggressive. Thus, life cycle of products it is becoming shorter, and that also due to the markets globalization. So, the development of models that can support NPD processes became a real and needed challenge. This paper aims to propose a comprehensive model of functional nature, which integrates the strategic, organizational and procedural levels, as well as the set of factors to take into account in NPD projects. Based on literature review, a comprehensive and integrated conceptual model is obtained through a deductiveinductive pathway. The conceptual model is validated in the industrial environment through four explanatory case studies, regarding the implementation of new products and services, both incremental and disruptive. After validation the conceptual framework becomes functional. And it was referred as “Systemic and Integrated Model of NPD” - SIMNPD. As a result, it is a tool to measure and evaluate processes, projects and products, dedicated to companies that innovate, design and develop new products.